Transcriptome analysis of the toxic mechanism of nanoplastics on growth, photosynthesis and oxidative stress of microalga Chlorella pyrenoidosa during chronic exposure. (1st September 2021) - Yang, Wenfeng; Gao, Pan; Ma, Guoyi; Huang, Jiayi; Wu, Yixiao; Wan, Liang; Ding, Huijun; Zhang, Weihao
Abstract: The toxicity of nanoplastics to aquatic organisms has been widely studied in terms of biochemical indicators. However, there is little discussion about the underlying toxic mechanism of nanoplastics on microalgae. Therefore, the chronic effect of polystyrene (PS) nanoplastics (80 nm) on Chlorella pyrenoidosa was investigated, in terms of responses at the biochemical and molecular/omic level. It was surprising that both inhibitory and promoting effects of nanoplastcis on C. pyrenoidosa were found during chronic exposure. Before 13 days, the maximum growth inhibition rate was 7.55% during 10 mg/L PS nanoplastics treatment at 9 d. However, the inhibitory effect gradually weakened with the prolongation of exposure time. Interestingly, algal growth was promoted for 1–5 mg/L nanoplastics during 15–21 d exposure. Transcriptomic analysis explained that the inhibitory effect of nanoplastics could be attributed to suppressed gene expression of aminoacyl-tRNA synthetase that resulted in the reduced synthesis of related enzymes. The promotion phenomenon may be due to that C. pyrenoidosa defended against nanoplastics stress by promoting cell proliferation, regulating intracellular osmotic pressure, and accelerating the degradation of damaged proteins and organs. This study is conducive to provide theoretical basis for evaluating the actual hazard of nanoplastics to aquatic organisms. Graphical abstract: Image 1 Highlights: Polystyrene nanoplastics have dual effects of inhibition and promotion on algae. Nanoplastics primarily inhibit gene expression of aminoacyl tRNA synthetase. Algal cells promote cell proliferation and degrade damaged proteins under stress. Regulating the intracellular osmotic pressure is also algal detoxification ability.